KARAKTER DUAL SITE ADSORBEN ABU LAYANG BATUBARA TERHADAP ADSORPSI ION Pb(II), METIL VIOLET DAN BENZENA - , WIDI ASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Large quantities of coal fly ash (CFA) are produced during the combustion of coal in the production of electricity. Most of this ash has not been widely used. CFA is mainly composed of some oxides such as Al2O3, SiO2, and unburned carbon that enables it to act as an adsorbent. In this research, the effect of CFA crystallinity and the presence of unburned carbon on CFA toward adsorption capacity for Pb(II) ion, methyl violet and benzene was reported. The effect of unburned carbon toward CFA adsorption capacity was studied by reducing and increasing carbon content. Oxidation process using sulfuric acid at various concentration, temperature, reaction time and combustion process at various temperature were used to reduce carbon content. While, reducing of non carbon mineral by 100 mesh-sieve was used to increase carbon content. The effect of coal fly ash crystallinity was studied by reducing the crystallinity using sodium hydroxide solution at various concentration, temperature and reaction time. The treated CFA was further used for Pb(II), methyl violet and benzene adsorption. Equilibrium data were also evaluated by single site and dual site isotherm models. It can be concluded that increasing carbon content gives high surface area and pore diameter. As a result, the adsorption capacity toward benzene increase, but the adsorption capacity toward Pb(II) ion and methyl violet decrease. The decrease of coal fly ash crystallinity gives high surface area and pore diameter. As a result, the adsorption capacity toward Pb(II) ion and methyl violet increase, but it is not significant for benzene. For Pb(II) ion, and methyl violet adsorption, the Langmuir model yielded excellent fit with equilibrium data for coal fly ash having ratio of [Si+Al]/Câ90, and Freundlich-Langmuir model yielded excellent fit with equilibrium data for coal fly ash having ratio of [Si+Al]/C â0,5 and [Si+Al]/C â2. While, for benzene adsorption, the Langmuir model yielded excellent fit with equilibrium data.